Allometric relationships shape foreleg evolution of long‐legged oil bees (Melittidae: Rediviva). (27th December 2020) - Melin, Annalie; Altwegg, Res; Manning, John C.; Colville, Jonathan F.
Abstract: Exaggerated traits of pollinators have fascinated biologists for centuries. To understand their evolution, and their role in coevolutionary relationships, an essential first step is to understand how traits scale allometrically with body size, which may reveal underlying developmental constraints. Few pollination studies have examined how traits can adaptively diverge despite allometric constraints. Here, we present a comparative study of narrow‐sense static and evolutionary allometry on foreleg length and body size of oil‐collecting bees. Concurrently, we assess the relationship between scaling parameters and spur lengths of oil‐secreting host flowers. Across species and populations, we found low variation in static slopes (nearly all <1), possibly related to stabilizing selection, but the static intercept varied substantially generating an evolutionary allometry steeper than static allometry. Variation in static intercepts was explained by changes in body size (∼28% species; ∼68% populations) and spur length (remaining variance: ∼36% species; ∼94% populations). The intercept–spur length relationship on the arithmetic scale was positive but forelegs did not track spur length perfectly in a one‐to‐one relationship. Overall, our study provides new insights on how phenotypic evolution in the forelegs of oil‐collecting bees is related to the variability of the allometric intercept and adaptation to host plants.